Attitudes toward uterus transplantation. An option for motherhood? - Mariona Rius; Marta Camacho; Nerea Tomás; Berta Díaz‐Feijoo; Camil Castelo‐Branco; Aina Borras; Jaume Tort; Francisco Carmona (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Uterus transplantation is a novel surgical procedure that allows women with absolute uterine factor infertility to carry a pregnancy and give birth. While previous studies have explored the attitudes of women with absolute uterine factor infertility toward uterus transplantation, none have surveyed and compare their views with other groups of interest (Morris syndrome women, relatives of Morris syndrome and Rokitansky syndrome women, infertile women and women of childbearing age) in the same sociocultural setting. The objective of this study was to evaluate attitudes and insights regarding uterus transplantation among women with Rokitansky syndrome and other groups of interest. Material and Methods We designed a cross‐sectional study including five groups of women: women with Rokitansky syndrome, women with Morris syndrome, relatives of women with Morris and Rokitansky syndrome, infertile women, and childbearing‐age women. We conducted an online survey through the REDCap platform. The link was distributed by mail, telephone and in hospital outpatient visits. Baseline demographic information was assessed and information regarding motherhood preferences, attitude toward uterus transplantation, preferred uterus graft and perception of risk of the procedure was collected. Results We obtained a total of 200 responses, with a mean participant age of 34.5 years (±9.8). Overall, 17.5% (n = 35) were women with Rokitansky syndrome, 5.5% (n = 11) Morris syndrome women, 21.5% (n = 43) infertile women, 26.5% (n = 53) relatives of Morris and Rokitansky syndrome women and 29% (n = 58) childbearing‐age women. 71.5% of women with Rokitansky syndrome would undergo uterus transplantations ahead of adoption and surrogacy with no statistically significant differences found between groups. Overall, more than one‐half (58%) would prefer deceased over living donor. Conclusions The results of this survey indicate that uterus transplantation is desired by most women who would benefit from the procedure, including those with either Morris syndrome or absolute uterine factor infertility. This was also the preferred option for motherhood if absolute uterine factor infertility was diagnosed among surveyed infertility patients or women of childbearing age with no known reproductive difficulties. Overall, most respondents indicated a deceased donor was preferable to a living donor and that patients may not be sufficiently aware of potential risks of uterus transplantation, highlighting the importance of adequate counseling by medical providers.